Economic forecasts and policy - Theil, Henri; Cramer, J.S.; Moerman, H.; Russchen, A. (Amsterdam : North-Holland Pub. Co., 1965)
The author provides a review of the mathematical theory of maximization subject to constraints, especially of the maximization of quadratic functions subject to linear constraints.
Includes bibliographical footnotes.
osa 06/11/2018
Loans
Keywords: Economic forecasting; Economics, Mathematical